Diversity of Endophytic Fungal Community Associated with Local Rice Varieties Commonly Grown in Kuantan Singingi, Riau Province, Indonesia - Andriani, Desta; Seprido; Ezward, Chairil (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2023)
In a natural ecosystem, the plant establishes a mutual relationship with beneficial endophytes contributing huge impact on its host plant. Therefore, exploring beneficial endophytic fungi identified in a wide range of host plant species and their interaction is an interesting area of study. The present work aimed to characterize the fungal endophytic communities associated with local rice varieties. Healthy local rice variety commonly grown in Kuantan Singingi (Padi Kuning, Padi Gondok, Padi Sironda Putih, and Padi Sironda Merah) were selected and sampled. The samples were taken from different plant parts (root, stem and leaf). Descriptive statistics were used to present the results of this study. Results obtained from the present study showed that a total of 8 isolates were found in Padi Kuning, 9 isolates in Padi Rondok, 11 isolates in เว็บสล็อต | R4shub Padi Sironda Putih, and 11 isolates in Padi Sironda Merah. From different tissue parts of the plant, a total of 14, 12, and 13 isolates was found in stem, leaf, and root, respectively. Comparisons of the stem, leaf and root samples demonstrate a similarity in the endophyte assemblages among the local rice varieties and plant parts.